2009
DOI: 10.1016/j.ygeno.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of methods for use of formalin-fixed, paraffin-embedded tissue samples in RNA expression profiling

Abstract: Formalin-fixed paraffin-embedded (FFPE) tissue samples are a potentially valuable resource of expression information for medical research, but are under-utilized due to degradation and modification of the RNA. Using a random primer-based RNA amplification strategy, we have evaluated multiple protocols for the extraction and isolation of RNA from FFPE samples. We found that the RecoverAll RNA isolation procedure with three or four slices (ten-microns in thickness), supplemented with additional DNAse, gave optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 21 publications
2
45
1
Order By: Relevance
“…Our results showed an almost perfect correlation (R 2 ¼ 0.97) between the microarray and qRT-PCR data. Together with other reports, 8,20 our results illustrated that formalinfixed and paraffin-embedded tissue material is valuable in evaluating the molecular pathology of neuroendocrine tumors-a particularly useful resource when fresh-frozen tissue is scarce. However, our data also suggest limited sensitivity of the formalin-fixed and paraffin-embedded tissue profiling approach.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our results showed an almost perfect correlation (R 2 ¼ 0.97) between the microarray and qRT-PCR data. Together with other reports, 8,20 our results illustrated that formalinfixed and paraffin-embedded tissue material is valuable in evaluating the molecular pathology of neuroendocrine tumors-a particularly useful resource when fresh-frozen tissue is scarce. However, our data also suggest limited sensitivity of the formalin-fixed and paraffin-embedded tissue profiling approach.…”
Section: Discussionsupporting
confidence: 81%
“…12 However, microarray analysis using formalin-fixed and paraffinembedded tissue is a new and evolving field. 8,20 The technical challenges of formalin-fixed and paraffin-embedded tissue profiling are significant, formalin fixation leads to degradation and chemical modification of the RNA with extensive cross-links between various biomolecules in the tissue, thus, hindering analysis. 21 However, significant improvements have been made in RNA isolation and amplification-a series of reports have suggested that gene profiling on formalin-fixed and paraffinembedded tissue material is now feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ct threshold was set to an arbitrary value of 0.067761 after averaging all plates and performing manual inspection for best-fit, while the baseline was set to 3 cycles below the lowest Ct. Afterwards, the Ct values for each sample were exported into separate Microsoft Excel files for webbased RT 2 Profiler PCR Array Data Analysis 3.5 (http://pcrdataanalysis.sabiosciences.com/pcr/arrayanalysis.php). Quantification of the relative changes of gene expression levels (fold-change) was performed using the 2 −ΔΔCt method.…”
Section: Discussionmentioning
confidence: 99%
“…However, the isolation and downstream analysis of nucleic acids from these samples are technically difficult due to chemical modifications and degradation associated with the fixation process and storage. 2 In particular, the presence of formaldehyde induces crosslinking between nucleic acids and proteins, and the low pH (<1) induces fragmentation. 3,4 Nevertheless, FFPE-archived tissues are more easily accessible than fresh or frozen tissues, thus much effort has been made to use FFPE tissues for different genetic analysis.…”
Section: Introductionmentioning
confidence: 99%